1999
DOI: 10.1152/ajplung.1999.276.2.l304
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 is elevated in monocrotaline pulmonary hypertension

Abstract: These studies document striking pulmonary vasoconstrictor response to nitric oxide synthase (NOS) inhibition in monocrotaline (MCT) pulmonary hypertension in rats. This constriction is caused by elevated endothelin (ET)-1 production acting on ETA receptors. Isolated, red blood cell plus buffer-perfused lungs from rats were studied 3 wk after MCT (60 mg/kg) or saline injection. MCT-injected rats developed pulmonary hypertension, right ventricular hypertrophy, and heightened pulmonary vasoconstriction to ANG II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
64
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 18 publications
8
64
0
Order By: Relevance
“…ET-1 was shown to induce expression of matrix and matrix-associated genes including CTGF in various cell types (Chaqour et al, 2002;Shi-Wen et al, 2004). The importance of ET-1 is also suggested by the previous reports which showed that ET-1 is elevated in patients with PH (Giaid et al, 1993) as well as in animal models of PH (Mansoor et al, 1995;Frasch et al, 1999). Therefore, it is very likely that TGF-β1, together with ET-1, plays an active role in the upregulation of CTGF in MCT-induced PH.…”
Section: Discussionmentioning
confidence: 68%
“…ET-1 was shown to induce expression of matrix and matrix-associated genes including CTGF in various cell types (Chaqour et al, 2002;Shi-Wen et al, 2004). The importance of ET-1 is also suggested by the previous reports which showed that ET-1 is elevated in patients with PH (Giaid et al, 1993) as well as in animal models of PH (Mansoor et al, 1995;Frasch et al, 1999). Therefore, it is very likely that TGF-β1, together with ET-1, plays an active role in the upregulation of CTGF in MCT-induced PH.…”
Section: Discussionmentioning
confidence: 68%
“…On the other hand, the Ghr-GHSR signaling pathway can revert ET-1-induced vasoconstriction by mechanisms that act by GH/IGF-1 and endothelium-independent pathways (21,37). It should be emphasized that ET-1 is increased in PH and seems to be largely involved in MCT-induced PH (10). With regard to pulmonary vascular remodeling, the present study showed that the medial area in peripheral pulmonary arteries was significantly reduced by Ghr, indicating that attenuation of PH is, at least partially, mediated by this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows thickening of pulmonary arteries at the light microscopic level. In the animal model of monocrotaline-induced pulmonary hypertension (67,68), endothelial ET-1 production is elevated and NO activity is decreased. The fact that deaths occur in animals of this model when exposed to particles raises the possibility that the same mechanism involved in response to monocrotaline is operative in response to particle inhalation.…”
Section: Discussionmentioning
confidence: 99%